Post-Harvest Non-Conventional and Traditional Methods to Control Cadophora luteo-olivacea: Skin Pitting Agent of Actinidia chinensis var. deliciosa (A. Chev.) - Alessandra Di Francesco; Michele Di Foggia; Alessio Vittoria; Elena Baraldi (Horticulturae, 2021)
Cadophora luteo-olivacea represents a critical problem for kiwifruit in the post-harvest phase, mainly for its little note epidemiology. The study presented some results about the possibility of preserving kiwifruit from skin pitting symptoms using alternative methods to fungicides. By in vitro assays, antagonist mechanisms of action against pathogen isolates were tested. Trichoderma harzianum (Th1) showed the highest inhibitory activity against C. luteo-olivacea isolates by volatile, non-volatile, and by dual culture assay, displaying an inhibition respectively by 90%, 70.6%, and 78.8%, and with respect to Aureobasidium pullulans (L1 and L8) by 23.3% and 25.8%, 50% and 34.7%, and 22.5% and 23.6%, respectively. Further, the sensitivity on CFU and mycelial growth of C. luteo-olivacea isolates to fludioxonil, and CaCl2 was tested, displaying interesting EC50 values (0.36 and 0.92 g L−1, 22.5 g L−1, respectively). The effect of Brassica nigra defatted meal was tested as biofumigation assays and through FT-IR (Fourier-Transform Infrared) spectroscopy. The above-mentioned treatments were applied in vivo to evaluate their efficacy on kiwifruits. Our data demonstrated that alternative solutions could be considered to control postharvest pathogens such as C. luteo-olivacea.